Study Of Public Perception And Analysis Of Regional Original Revenue (Pad) And General Allocation Fund (Dau) On Economic Growth With Government Spending As A Moderation - Muhammad Saleh; Ahmad Rifani; Rahmatullah Alfikri (Cita Konsultindo Research Center, 2025)
Revenue receipts of Hulu Sungai Selatan Regency during the period 2004-2023 shows average growth annual by 18.82%. DAU receipts recorded growth annual by 7.62%, spending area by 13.60%, and growth economy by 4.79% per year. Research this aiming to (1) analyze influence simultaneous PAD and DAU towards growth economy HSS Regency ; (2) analyze influence partial PAD and DAU against growth economy ; (3) testing role shopping government as variable moderation in the relationship between PAD and DAU with growth economy ; and (4) understanding impact growth economy to welfare public HSS Regency . Research uses a Mixed Method approach with multiple linear regression analysis tools and Moderated Regression Analysis (MRA). Samples were taken as many as 800 people with multi-stake random sampling, where samples were spread across all sub-districts and village sampling to RT throughout Hulu Sungai Selatan Regency. Analysis results multiple linear regression show that (a) PAD and DAU are simultaneous influential significant to growth economy; (b) PAD does not influential to growth economy and DAU has an influence significant to growth economy; (c) shopping area No capable to moderate PAD relationship to growth economy; and (d) shopping area also not to moderate DAU's relationship to growth economy.